PENGARUH KINERJA KEUANGAN DENGAN INFLASI SEBAGAI VARIABEL MODERASI TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Adrian Fatah Kobar (2020)
This research is a quantitative study that aims, among others to determine the effect of profitability, leverage, and earnings per share on stock returns. The sample in this study is manufacturing industry companies listed on the Indonesia Stock Exchange period 2017 - 2019. The sampling technique used in this study is the purposive sampling method. The research sample was 58 companies with 174 observations. Hypothesis testing in this study used regression analysis and also Moderate Regression Analysis (MRA) with E-Views 10.0 program. The results of test were obtained (1) there is no significant effect of profitability on stock returns, (2) there is no significant effect of solvency on stock returns, (3) there is a significant effect of earnings per share on stock returns. (4) partially, inflation cannot moderate the effect of profitability, solvency, and earnings per share.